Pharmacological profile of mephedrone analogs and related new psychoactive substances. (15th May 2018) - Luethi, Dino; Kolaczynska, Karolina E.; Docci, Luca; Krähenbühl, Stephan; Hoener, Marius C.; Liechti, Matthias E.
Abstract: Background: Mephedrone is a synthetic cathinone and one of the most popular recreationally used new psychoactive substances. The aim of the present study was to characterize the in vitro pharmacology of novel analogs of mephedrone and related newly emerged designer stimulants. Methods: We determined norepinephrine, dopamine, and serotonin transporter inhibition potencies and monoamine release in transporter-transfected human embryonic kidney 293 cells. We also assessed monoamine receptor and transporter binding affinities. Results: Mephedrone analogs potently inhibited the norepinephrine transporter and, with the exception of 3-methylmethcathinone (3-MMC), inhibited the serotonin transporter more potently than the dopamine transporter. Similar to classic amphetamines, mephedrone analogs were substrate-type monoamine releasers. 5-(2-Aminopropyl)indole (5-IT) was a highly potent monoamine transporter inhibitor and a releaser of dopamine and serotonin. 4-Methylamphetamine (4-MA) mediated efflux of all three monoamines and inhibited the serotonin transporter more potently than the dopamine transporter, unlike amphetamine. N -methyl-2-aminoindane ( N -methyl-2-AI) was a selective norepinephrine transporter inhibitor and norepinephrine releaser, whereas 5-methoxy-6-methyl-2-aminoindane (MMAI) was a selective serotonin transporter inhibitor and serotonin releaser. All of the drugs interacted with monoamine receptors. Conclusion: The predominant actions on serotonin vs. dopamine transporters suggest that dimethylmethcathinones, 4-MA, and MMAI cause entactogenic effects similar to 3, 4-methylenedioxymethamphetamine, whereas 3-MMC, 5-IT, and N -methyl-2-AI have more stimulant-type properties like amphetamine. Because of pharmacological and structural similarity to mephedrone, similar health risks can be expected for these analogs. This article is part of the Special Issue entitled 'Designer Drugs and Legal Highs.' Highlights: New designer drug analogs of mephedrone were characterized in vitro . Mephedrone analogs potently interacted with monoamine transporters suggesting abuse liability. In vitro serotonergic vs. dopaminergic properties were used to predict clinical effects.